Krisis Kepercayaan Publik: Kritis Terhadap Pengesahan Undang-undang Perampasan Aset Pada Akun @dpr_ri - Namira Azzahra Putriaji; Roma Kyo Kae Saniro; Anggun Putri Herlina; Hasyif Raqi Al Fadhen; Nanda Gita Aurellia; Rori Islami Sandika; Wulan Sari; Danial Julianda; Nayaka Artalya Marela (CV. ITTC INDONESIA, 2025)
This study aims to analyze lexical meaning, situational meaning, and the intended purpose conveyed in comments related to the issue of the